Plate II: Artist study of male heads and female head/torso - Salmon, William (Polygraphice, or, the Arts of Drawing, Engraving, Etching, Limning, Painting, Washing, Varnishing, Gilding, Colouring, Dying, Beautifying and Perfuming, 1685)
Engraved artist study of male heads as well as a female head and torso. The most popular of William Salmon's numerous books, the title page refers to 25 plates within whereas other copies are also missing plates 3 and 10, as is the case with this particular copy. Select digitized content includes front cover, frontismatter, engraved portrait frontispiece of Salmon (age 27 in 1675), engraved title page (both by W. Sherwin) as well as recto and versos of extant copperplate engravings. Plates 22 and 23 are misbound between plates 17 and 18.
Keywords: Art metal-work; Drawing--Technique; Salmon, William, 1644-1713; Portrait painting--Technique; Beauty, Personal; Painting--Technique; Sherwin, William; Art--Early works to 1800